A trama paradoxal do ódio no psiquismo - Barros, Maria Neuma Carvalho de (2014)
Hatred ― one of the main constituent elements in one s relationship with other people― is a kind of affection that may engender rejection. From a psychoanalytical perspective, it protagonizes the self s subjective structuring process and, at times, contributes to psychic preservation, as revealed in clinical practice. Thence, the need to start this work by posing the following question: how does hatred work in the psychic structure? This research is meant to be an extension of clinical practice and of our previously developed studies. To achieve this goal, we have resorted to some of the concepts of three major psychoanalists and authors: S. Freud, M. Klein and D. W. Winnicott. Considering their concepts on both the self and human psychism, we have detected in their theories pieces of information which are basic to the understanding of the presence of hatred in psychic dynamics; in addition to this, we have here examined some present day scholars contributions to our theme. All of these materials have helped us perceive the paradoxical plot created by the ambivalence of this affection in psychic dynamics, where it works not only to build up the self s structure and affirmation, but also as an element of resistance and destructiveness. Moving from theory to clinical practice ― and thus reinforcing the active articulation between both these poles, as recommended by psychoanalysis ― we have also resorted to clinical fragments to illustrate our major argument. The clinical examples here reported suggest, in short, that hatred can be equally used as a defense ― as evidenced, for example, in the analytical process ―, thus modifying the development of the psychic plot. Finally, we do believe that this investigation can eventually contribute to the work of those who dedicate themselves to psychoanalytical practice and the study of psychoanalysis, particularly as regards the complex and revealing expressions of hatred, which are characteristic of the human condition.